LEXICOGRAPHIC ANALYSIS MECHANISM OF BUSINESS AND ENTREPRENEURSHIP TERMS IN LANGUAGES - Kamilova Durdona Kozimdzhanovna (Bright Mind Publishing, 2025)
This article studies the comparative analysis of business and entrepreneurship terms in English and Uzbek based on a lexicographic approach. First, a theoretical approach to the concepts of dictionary and lexicography is presented, and the principles of dictionary construction, its historical development, and practical significance are analyzed. The formation, use, and translation problems of business terms in Uzbek and English are considered topical issues in linguistics. At the same time, existing business dictionaries, their structure, and functional tasks are analyzed comparatively. Lexicographic sources, especially multilingual and specialized dictionaries, show the global impact of business terminology in English in connection with the international status of the English language. In conclusion, based on a comparative analysis, common (universal), different, and unique features of the languages are identified.
Keywords: Lexicography, business terms, entrepreneurial lexicon, English and Uzbek languages, vocabulary, comparative analysis, dictionary creation, industry terminology, linguistics, multilingual dictionary.